INFLUENCE OF PHOSPHORUS-POTASSIUM RATIOS ON MAIZE GROWTH, NUTRIENT DYNAMICS, AND YIELD IN CONTRASTING ECOLOGICAL ZONES OF SOUTHERN NIGERIA - Bakare, A.O.; Efenudu, I.U. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study evaluated the influence of varying soil phosphorus-potassium (P:K) ratios on maize (Zea mays L.) growth, nutrient availability, and yield in two distinct ecological zones of Edo State, Nigeria: the rainforest (RRIN-Iyanomo) and derived savanna (Ambrose Alli University Farm, Emaudo). Using a randomized complete block design with ten P:K treatments (0:0, 1:1, 2:1, 3:1, 4:1, 5:1, 1:2, 1:3, 1:4, 1:5) replicated thrice in pot and field experiments. Pre-planting soil analysis revealed acidic soils with low organic carbon, nitrogen, and exchangeable potassium. Key results indicated that P:K ratios significantly altered maize performance. In RRIN (forest), the 1:3 P:K ratio maximized dry matter yield (5.20 g/pot), plant height (201.0 cm), and grain yield (2.97 t/ha). Conversely, in Emaudo (savanna), the 1:4 ratio optimized growth (plant height: 106.0 cm; stem girth: 1.67 cm) and grain yield (2.74 t/ha). Potassium-dominated ratios (1:2, 1:3) enhanced K uptake and photosynthetic efficiency, while P-dominated treatments (4:1, 5:1) increased P concentration but reduced yields. Correlation analysis confirmed strong relationships between K uptake and dry matter yield (RRIN: *r* = 0.858; Emaudo: *r* = 0.782). The study demonstrates ecological zone-specific P:K optimization: 1:3 in rainforests and 1:4 in derived savannas. These ratios improve nutrient use efficiency and maize productivity while mitigating fertilizer overuse in fragile tropical soils.